Effect of conventional multilevel brachycephalic obstructive airway syndrome surgery on clinical and videofluoroscopic evidence of hiatal herniation and gastroesophageal reflux in dogs. Issue 2 (23rd October 2022) - Mayhew, Philipp D.; Marks, Stanley L.; Pollard, Rachel; Balsa, Ingrid M.; Culp, William T. N.; Giuffrida, Michelle A.
Abstract: Objective: To evaluate the effect of conventional multilevel surgery (CMS) for brachycephalic obstructive airway syndrome (BOAS) on associated sliding hiatal hernia (SHH) and/or gastroesophageal reflux (GER). Study design: Prospective clinical trial. Animals: Sixteen client‐owned dogs with clinical signs consistent with BOAS and associated SHH and GER. Methods: All dogs were treated with 1 or more components of CMS including soft palate resection, laryngeal ventriculectomy, and alaplasty. A standardized Dog Swallowing Assessment Tool (Dog SAT) questionnaire was completed by owners preoperatively and postoperatively. Videofluoroscopic swallow studies (VFSS) were used to evaluate esophageal motility, gastroesophageal reflux, and hiatal herniation preoperatively, and in a subset of dogs postoperatively. Upper gastrointestinal endoscopic studies were performed to document esophagitis and lower esophageal sphincter pathology. Results: All dogs were discharged from the hospital. One dog experienced aspiration pneumonia immediately postoperatively. Owner‐assigned clinical scores improved in scores related to regurgitation after eating and regurgitation ( P  = .012) during increased activity/exercise ( P  = .002) between preoperative and postoperative time points. However, no improvement was detected in masked assessment of preoperative and postoperative VFSS studies in terms of GER frequency ( P  = .46) or severity ( P  = .79), SHH frequency ( P  = .082) or severity ( P  = .34) scores. Conclusion: Owners of dogs treated with CMS perceived an improvement in clinical signs of SHH and GER that was not confirmed by VFSS studies. Clinical significance: Conventional multilevel surgery in dogs with BOAS does not appear to consistently resolve SHH and GER, although clinical signs may improve.